Drebrin expression patterns in patients with refractory temporal lobe epilepsy and hippocampal sclerosis. (14th July 2020) - Dombroski, Thaís Caroline Dallabona; Peixoto‐Santos, Jose Eduardo; Maciel, Karina; Baqui, Munira Muhammad Abdel; Velasco, Tonicarlo Rodrigues; Sakamoto, Americo Ceiki; Assirati, João Alberto; Carlotti, Carlos Gilberto; Machado, Hélio Rubens; Sousa, Gleice Kelly de; Hanamura, Kenji; Leite, João Pereira; et al.
Abstract: Objective: Drebrins are crucial for synaptic function and dendritic spine development, remodeling, and maintenance. In temporal lobe epilepsy (TLE) patients, a significant hippocampal synaptic reorganization occurs, and synaptic reorganization has been associated with hippocampal hyperexcitability. This study aimed to evaluate, in TLE patients, the hippocampal expression of drebrin using immunohistochemistry with DAS2 or M2F6 antibodies that recognize adult (drebrin A) or adult and embryonic (pan‐drebrin) isoforms, respectively. Methods: Hippocampal sections from drug‐resistant TLE patients with hippocampal sclerosis (HS; TLE, n = 33), of whom 31 presented with type 1 HS and two with type 2 HS, and autopsy control cases (n = 20) were assayed by immunohistochemistry and evaluated for neuron density, and drebrin A and pan‐drebrin expression. Double‐labeling immunofluorescences were performed to localize drebrin A–positive spines in dendrites (MAP2), and to evaluate whether drebrin colocalizes with inhibitory (GAD65) and excitatory (VGlut1) presynaptic markers. Results: Compared to controls, TLE patients had increased pan‐drebrin in all hippocampal subfields and increased drebrin A–immunopositive area in all hippocampal subfields but CA1. Drebrin‐positive spine density followed the same pattern as total drebrin quantification. Confocal microscopy indicated juxtaposition of drebrin‐positive spines with VGlut1‐positive puncta, but not with GAD65‐positive puncta. Drebrin expression in the dentate gyrus of TLE cases was associated negatively with seizure frequency and positively with verbal memory. TLE patients with lower drebrin‐immunopositive area in inner molecular layer (IML) than in outer molecular layer (OML) had a lower seizure frequency than those with higher or comparable drebrin‐immunopositive area in IML compared with OML. Significance: Our results suggest that changes in drebrin‐positive spines and drebrin expression in the dentate gyrus of TLE patients are associated with lower seizure frequency, more preserved verbal memory, and a better postsurgical outcome.